Bibliometric Analysis of Chemistry Publication Trends on Scopus in The Era of Big Data - Bakti, Andi Budi (Prodi Kimia, 2024)
In the 21st century, chemistry has seen a major shift in data management practices. Analyzing research trends is crucial for maintaining relevance and innovation. This study aims to: (1) identify the contributions of researchers and institutions and assess their impact; (2) map the network of interactions among publications, references, topics, researchers, and institutions; and (3) predict future directions and recommend research opportunities in chemistry. This study employs bibliometric analysis and science mapping techniques with VOSviewer. The study finds that: (1) J. M. Cole and the United States are the leading contributors; (2) big data research in chemistry is not yet deeply and continuously explored, with researchers often working in small groups and focusing on topics such as